Faktor yang Memengaruhi Perilaku Menabung pada Generasi Z di Kecamatan Gebang, Kabupaten Langkat - Agusty, Mutiara; Wahyuni, Sri Fitri; Radiman, Radiman (https://jurnal.binamandiri.ac.id/, 2024)
This research analyzes the influence of income, financial literacy, self-control and risk tolerance on saving behavior. This research adopts a quantitative associative methodology, where everyone from generation Z who lives in the Gebang District, Langkat Regency, is the sample population. The Lemeshow method was used to determine the sample size, which determined a minimum of 96 respondents to participate in filling out a questionnaire on a Likert scale. The data collected was then analyzed using the PLS-SEM approach with the SmartPLS tool. Research findings reveal that financial literacy, income, self-control ability, and readiness to face risks influence how generation Z in the area spends and saves. Thus, this research provides deeper insight into how these aspects are interconnected and influence individual savings habits among generation Z.